ПРОБЛЕМИ РОЗВИТКУ МЕТОДУ РЕНТГЕНІВСЬКОЇ ФОТОЕЛЕКТРОННОЇ СПЕКТРОСКОПІЇ В УКРАЇНІ - Korduban, Oleksandr; Ogenko, Volodymyr; Kryshchuk, Taras (V.I.Vernadsky Institute of General and Inorganic Chemistry, 2021)
The article is devoted to the development problems of the X-ray Photoelectron Spectroscopy (XPS) method in Ukraine. XPS is a modern method for studying the electronic structure of atoms. The XPS method is used at all stages of the synthesis and study of materials, the functional properties of which are determined by the state of the surface or interphase boundaries, charge states of atoms and the type of functional groups, and material degradation processes. The objects of study are catalysts, coatings, chemical sensors, sorbents, coordination and organometallic compounds (chemistry, materials science, pharmaceuticals), surface condition and composition (microelectronics), thin films (optics), alloys (aviation and space industry), nanopowders, nanofilms (nanotechnology). The method is relevant for the implementation of targeted synthesis of materials. In the world, the XPS method is widespread and integrated into innovative branches of science and technology, and XPS - instrumentation - is a high-tech business. In Ukraine, the method is practically not presented, there is no competition in this field of instrumentation. The article proposes the creation on the basis of the National Academy of Sciences of Ukraine a park of unitary, high-quality and affordable domestic XPS-spectrometers and the opening of a service center. The XPS method is necessary for most of the institutes of the National Academy of Sciences of Ukraine from the departments of chemistry, physics and astronomy, physical and technical problems of materials science, earth sciences and all specialized faculties of state universities. In general, for Ukraine, this is at least 50 spectrometers. The mechanism for the implementation of the project can be the formation of a state order for the development and manufacture of a batch of XPS spectrometers on the basis of imported and domestic components (50:50) and attracting business to the project. Creation of a network of Domestic XPS-spectrometers allows to obtain a sharp increase in the efficiency of scientific research in chemistry, physics, materials science and is one of the conditions for Ukraine’s transition to an innovative economy.